2016
DOI: 10.1093/nar/gkw1273
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis SWI/SNF chromatin remodeling complex binds both promoters and terminators to regulate gene expression

Abstract: ATP-dependent chromatin remodeling complexes are important regulators of gene expression in Eukaryotes. In plants, SWI/SNF-type complexes have been shown critical for transcriptional control of key developmental processes, growth and stress responses. To gain insight into mechanisms underlying these roles, we performed whole genome mapping of the SWI/SNF catalytic subunit BRM in Arabidopsis thaliana, combined with transcript profiling experiments. Our data show that BRM occupies thousands of sites in Arabidops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
69
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 78 publications
(112 reference statements)
10
69
0
1
Order By: Relevance
“…Both H2A.Z and BRM contribute to transcriptional repression and transcriptional activation, but it is unknown how the role of one factor at a gene might affect the role of the other in transcriptional regulation. (Marques et al ., ; Archacki et al ., ). To identify the genes in Arabidopsis that are transcriptionally regulated by BRM and H2A.Z, we performed RNA sequencing (RNA‐seq) experiments.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Both H2A.Z and BRM contribute to transcriptional repression and transcriptional activation, but it is unknown how the role of one factor at a gene might affect the role of the other in transcriptional regulation. (Marques et al ., ; Archacki et al ., ). To identify the genes in Arabidopsis that are transcriptionally regulated by BRM and H2A.Z, we performed RNA sequencing (RNA‐seq) experiments.…”
Section: Resultsmentioning
confidence: 97%
“…From this point on in the study, we focused our analysis on the DE BRM and H2A.Z target genes and considered their transcription to be directly regulated by H2A.Z and/or BRM. Collectively, the defined DE target genes support the notion that both BRM and H2A.Z contribute to gene repression and activation in different contexts (Marques et al ., ; Archacki et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In that work we demonstrated that the chromatin remodeler BRM could promote gene expression by limiting the deposition of H3K27me3 through suppressing the recruitment and/or the activity of CLF/SWN. Therefore, to find out whether the lack of H3K27me3 deposition is due to the presence of BRM, we checked the BRM occupancy at those CLF/SWN targets (Archacki et al., ; Li et al., ). Indeed, we saw nearly half of these genes (63 out of 136) were bound by BRM as well (Supporting Information ).…”
Section: Resultsmentioning
confidence: 99%
“…The genomic region of DOG1 that differentiates shDOG1 and lgDOG1 (2nd intron/3rd exon) contains a promoter in the antisense orientation, which drives asDOG1 expression (Fedak et al ) (Figure ). The expression of antisense RNA from terminator regions may be a common phenomenon (Lin et al ; Archacki et al ). In the case of DOG1 , the expression of asDOG1 negatively regulates sense DOG1 expression, presumably through transcriptional control (possible mechanisms summarized in Nonogaki ) and reduces seed dormancy (Fedak et al ).…”
Section: Seed Dormancymentioning
confidence: 99%